(untitled) (Journal of Music Research Online, 2022)
In this paper, I attempt to trace the music theorist Johannes de Grocheio, author of the Ars musice (ca. 1275). I consider his Norman background, the two monks responsible for preserving his only known treatise, and his disputed magisterial standing in the university city of Paris. I then focus on Grocheio’s treatment of chant theory, which has received scant attention in the literature compared with his remarks on secular music and his ‘Aristotelian’ method of describing his subject. I contemplate the social context for writing anew on chant theory in a city known for not stipulating music in its arts curricula and consider the influence of Aristotle’s writings on Grocheio’s treatment. I end the paper with a survey of the chants that he names in his treatise, confirming that his examination of chant is ‘according to the use of the people of Paris’.